El ferrocarril y su aporte al turismo en el cantón Yaguachi - Suarez Méndez, Selena Danesa (2020)
The present case study focuses on the promotion of the Yaguachi canton railway, it will try to analyze the most important aspects and thus boost the tourist contribution that this generates in the population, so it is important to describe the different variables that make up this study. To understand the relationship they present with each of their determinations, they intend to analyze the most significant points that make it possible to promote this tourist attraction; Not only will it provide an influx of visitors in the sector, but it will also allow the economic growth of the canton, indirectly involving the nearest populations. This study focuses directly on tourism as a source of livelihood to balance the conditions that make up the tourism plant.